Negative Affectivity and Maladaptive Coping Strategies in Depressed Adolescents’ Family Conflict Management: The Mediating Role of Emotional Flexibility - Heidarnezhad , Shahla; Haddadi, Ruholla; Zomorodi, Saeedeh (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective:  This study aimed to examine the direct and indirect effects of negative emotionality and maladaptive coping strategies on family conflict management among depressed adolescents, with emotional flexibility as a mediating variable.Methods and Materials: The present research employed a descriptive–correlational design using structural equation modeling. The statistical population consisted of all female students enrolled in upper secondary education in two high schools in District 2 of Tehran during the 2024–2025 academic year, from which 234 adolescents diagnosed with mild to moderate depression were selected based on the Morgan table. Participants completed the Negative Emotionality Questionnaire, the short form of the Coping Inventory for Stressful Situations, the Emotional Flexibility Questionnaire, and the Conflict Tactics Scale. Data were analyzed using Pearson correlation coefficients and structural equation modeling in SPSS 24 and AMOS 24 after confirming normal distribution of variables through the Kolmogorov–Smirnov test.Findings: Structural equation modeling indicated that negative emotionality exerted a significant direct negative effect on family conflict management (β = −0.218, T = 2.845, p < .05), whereas maladaptive coping strategies demonstrated a significant direct positive effect (β = 0.247, T = 3.617, p < .05). Emotional flexibility showed a significant direct negative effect on family conflict management (β = −0.343, T = 6.604, p < .001). Furthermore, negative emotionality significantly predicted emotional flexibility (β = 0.244, T = 3.261, p < .01), while maladaptive coping strategies significantly predicted emotional flexibility in a negative direction (β = −0.328, T = 6.120, p < .001). Sobel test results confirmed the mediating role of emotional flexibility in the relationships between negative emotionality and family conflict management (Z = 2.201, p < .05) and between maladaptive coping strategies and family conflict management (Z = 2.782, p < .01).Conclusion: The findings demonstrate that emotional flexibility is a central psychological mechanism through which negative emotionality and maladaptive coping strategies influence family conflict management in depressed adolescents, suggesting that enhancing emotional flexibility may substantially improve relational functioning and emotional well-being.